PREVALENCE OF HIV INFECTION AMONG RURAL RESIDENTS OF EMOHUA L.G.A, RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
HIV/AIDS remains a significant public health challenge in Nigeria, particularly in rural areas where access to healthcare services is limited. This study aims to determine the prevalence of HIV infection among rural residents of Emohua Local Government Area (L.G.A) in Rivers State, Nigeria. A cross-sectional study was conducted from January to June 2024, involving 500 randomly selected participants aged 15-64 years from various rural communities within Emohua L.G.A. Data were collected using structured questionnaires and blood samples were tested for HIV antibodies using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Statistical analysis was performed using SPSS version 25.0. The overall prevalence of HIV infection among the study population was found to be 4.8%. The prevalence was higher among females (6.2%) compared to males (3.4%). Age-specific prevalence rates indicated the highest infection rate among individuals aged 25-34 years (7.1%), followed by those aged 35-44 years (5.5%). Factors significantly associated with higher HIV prevalence included low educational attainment, lack of awareness about HIV transmission, and limited access to healthcare services. The study highlights a significant burden of HIV infection among rural residents of Emohua L.G.A, with notable gender and age disparities. There is an urgent need for targeted HIV prevention and education programs, improved healthcare access, and community-based interventions to reduce the spread of HIV in these rural communities.